Surveillance Capitalism Revealed: Tracing The Hidden World Of Web Data Collection - Medeiros, Antony Seabra de; Glatzl Junior, Luiz Afonso; Lifschitz, Sérgio (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais Estendidos do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
This study investigates the mechanisms of Surveillance Capitalism, focusing on personal data transfer during web navigation and searching. By analyzing network traffic, we uncover how various entities track and harvest digital footprints. The research reveals specific data types exchanged between users and web services, emphasizing the sophisticated algorithms involved in these processes. We present concrete evidence of data harvesting practices and propose strategies for enhancing data protection and transparency. Our findings highlight the need for robust data protection frameworks and ethical data usage to address privacy concerns in the digital age.